KAJIAN AGRIBISNIS USAHA GULA AREN DI KABUPATEN REJANG LEBONG - Budiman, Yulius; Sukiyono, Ketut; Sumantri, Bambang (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
The research objectives are to 1) investigae the patternof input supplyin palm sugar industries; 2) determinethe factors that influenced palm sugar production, 3) examine important and need to increase attributes of agribusines marketing and financial institutions, and 4) analyze the degree of palm sugar producers’ satisfaction toward marketing and finance instituion services. The research location is selected using two metode stage cluster area sampling, starting from selecting two subdistricts, i.e., Sindang Kelingi and Selupu Rejang, followed by selecting two villages, i.e, Sindang Jati and Air Meles Atas. The criteria are based on the number of industries on each region selected. Eighty six respondents are selected using simple random sampling. To answer the purposes of this research, the research uses descriptive analysis, quantitative analysis of Cobb-Douglas function, Importance Performance Analysis (IPA) method and Customer Satisfaction Index (CSI) method. The research result shows that the inputs used the palm sugar productionare from buying, their owned, and rented. The result also shows that the volume of nira is important input in palm sugar production, while other factors, i.e., firewood, man labor, woman labor, are not. Important attributes of marketing institutions are the trader’s price discrimination toward the quality of palm sugar, providing the right information of price, the timing in giving information of price, and the accepting of the trader to appreciate and serving the need of the palm sugar producers. While important attributes of financial institutions include right time of disbursement, the ability of giving services to the palm sugar producers, the ability in helping process of borrow to the palm sugar producers, the ability of giving information to the palm sugar producers with easy language and easy to understand, honestly and patient in giving serve to the palm sugar producers, and providing enough time in serving palm sugar producers. Further, the result show that CSI of quality service of the marketing insitutionis 85,80%, meaning that palm sugar producers are really satisfy with the works af marketing institution. While CSI attributes to serve by financial institution is 80,55% indicating that the palm sugar producers are also satisfy with the work of financial instituions.